Five-year lapsed: Review of laparoscopic myomectomy versus open myomectomy in Putrajaya Hospital - Emily Christine D'Silva; Aisyah Munirah Muda; Anis Iryani Safiee; Wan Ahmad Hazim Wan Ghazali (Wolters Kluwer Medknow Publications, 2018)
Study Objective: This study aimed to investigate the morbidity of laparoscopic myomectomy (LM) versus open myomectomy (OM), including intraoperative blood loss, duration of surgery, hospital stay, and complications and to evaluate the criteria for selection of cases suitable for LM. Design: This was a retrospective study. Setting: This study was conducted at tertiary hospital. Participants: The records of 67 women who underwent LM, 22 women who underwent OM, and 14 women who had laparo-conversion from January 2010 to November 2014 were reviewed. Measurement and Main Results: Fibroids up to 10 cm were removed by LM, while most fibroids more than 10 cm were managed through OM. The number and weight of myomas are significantly associated with laparo-conversion, with a rate of 17%. Mean blood loss was significantly reduced in LM group than the OM and laparo-conversion groups. Duration of hospital stay was also significantly less in LM (2 ± 1 days) compared to both OM and laparo-conversion groups (3 ± 1 days). Most women underwent LM (88%) had no postoperative complications compared to OM (50%) and laparo-conversion (57.1%). The number of fibroids removed and duration of surgery was positively correlated with blood loss in the women who underwent myomectomy. Conclusion: LM is an ideal surgical approach for removal of fibroids which are up to 10 cm diameter and <5 in number, while OM is useful for cases with multiple (5 or more), larger fibroids (>10 cm), and deeply located fibroids. Preoperative evaluation of the size and number of myomas is necessary to avoid laparo-conversion and to reduce intraoperative and postoperative complications.